Oral health‐related knowledge, attitudes and self‐efficacy of Australian rural older adults. (15th July 2015) - Mariño, Rodrigo; Hopcraft, Matthew; Ghanim, Aghareed; Tham, Rachel; Khew, Chee‐Wah; Stevenson, Christine
Abstract : Objective: A cross‐sectional study was conducted involving older adults from social clubs within a regional local government area in the state of Victoria, Australia, to identify factors associated with knowledge, and attitudes about oral health, as well as perceived self‐efficacy. Methods: Participants underwent an oral health interview, followed by a comprehensive oral clinical examination. Results: A total of 225 older adults participated in this study. The mean age was 70.7 (range: 55–96) years. The majority was females (62.0%) and had incomplete secondary education or less (56.1%); 34.2% were fully edentulous. The mean oral health knowledge score was 24.7 (SD 3.8). None of the socio‐demographic and oral health variables yielded a significant effect on the knowledge score. The attitude score had a mean of 5.0 (SD 1.6). Four variables remained significant in the multivariate analysis [ p < 0.0001]. A dentate female, with tertiary education, had better oral health attitudes. Higher oral health knowledge scores were associated with a better attitude. The overall self‐efficacy mean value was 83.1% (SD 10.6). Dental visits and oral health knowledge remained significant in the attitudes multivariate analysis [ p < 0.01]. Conclusion: Findings indicate that there were some misconceptions in oral health among this group of older adults. These are important influences on the success/failure of an oral health programme. Oral health education is needed to increase older adults' oral health knowledge, in particular of oral cancer, and to some extent periodontal disease, and improves attitudes and oral health self‐efficacy. Oral health knowledge, attitudes and self‐efficacy were minimally explained by socio‐demographic and clinical variables.